A bit of trigonometry and algebra

Geometry Level 2

Given that cos 2 θ = 1 3 \cos2\theta=-\frac{1}{3} , find the value of sin 6 θ cos 6 θ \sin^6\theta-\cos^6\theta .

7 27 -\frac{7}{27} 1 3 -\frac{1}{3} 1 3 \frac{1}{3} 7 27 \frac{7}{27}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Marco Brezzi
Aug 14, 2017

Identities I'll use:

a 3 b 3 = ( a b ) ( a 2 + a b + b 2 ) a^3-b^3=(a-b)(a^2+ab+b^2)

sin 2 θ + cos 2 θ = 1 \sin^2{\theta}+\cos^2{\theta}=1

sin ( 2 θ ) = 2 sin θ cos θ \sin (2\theta)=2\sin\theta\cos\theta

cos ( 2 θ ) = cos 2 θ sin 2 θ \cos (2\theta)=\cos^2\theta -\sin^2\theta

Hence

sin 6 θ cos 6 θ = ( sin 2 θ ) 3 ( cos 2 θ ) 3 = ( sin 2 θ cos 2 θ ) ( sin 4 θ + sin 2 θ cos 2 θ + cos 4 θ ) = [ cos ( 2 θ ) ] ( sin 4 θ + cos 4 θ + 2 sin 2 θ cos 2 θ sin 2 θ cos 2 θ ) = 1 3 [ ( sin 2 θ + cos 2 θ ) 2 sin 2 θ cos 2 θ ] = 1 3 [ 1 2 sin 2 ( 2 θ ) 4 ] = 1 3 [ 1 1 cos 2 ( 2 θ ) 4 ] = 1 3 ( 1 1 1 9 4 ) = 1 3 ( 1 2 9 ) = 1 3 7 9 = 7 27 \begin{aligned} \sin^6\theta-\cos^6\theta &=(\sin^2\theta)^3-(\cos^2\theta)^3\\ &=(\sin^2\theta -\cos^2\theta)(\sin^4\theta+\sin^2\theta\cos^2\theta+\cos^4\theta)\\ &=[ -\cos(2\theta)](\sin^4\theta +\cos^4\theta +2\sin^2\theta\cos^2\theta-\sin^2\theta\cos^2\theta)\\ &=\dfrac{1}{3}[(\sin^2\theta+\cos^2\theta)^2-\sin^2\theta\cos^2\theta]\\ &=\dfrac{1}{3}\left[1^2-\dfrac{\sin^2(2\theta)}{4}\right]\\ &=\dfrac{1}{3}\left[1-\dfrac{1-\cos^2(2\theta)}{4}\right]\\ &=\dfrac{1}{3}\left(1-\dfrac{1-\frac{1}{9}}{4}\right)=\dfrac{1}{3}\left(1-\dfrac{2}{9}\right)=\dfrac{1}{3}\cdot\dfrac{7}{9}=\boxed{\dfrac{7}{27}} \end{aligned}

Didn't think of using sin ( 2 θ ) = 2 sin θ cos θ \sin\left(2\theta\right)=2\sin\theta\cos\theta . Nice!

Philip Lee - 3 years, 10 months ago

Dude, l just wanna say your solutions are outstanding. Neat and logical.

Hana Wehbi - 3 years, 9 months ago
Chew-Seong Cheong
Aug 14, 2017

cos 2 θ = 1 3 cos 2 θ sin 2 θ = 1 3 sin 2 θ cos 2 θ = 1 3 ( sin 2 θ cos 2 θ ) 3 = ( 1 3 ) 3 sin 6 θ 3 sin 4 θ cos 2 θ + 3 sin 2 θ cos 4 θ cos 6 θ = 1 27 sin 6 θ 3 sin 2 θ cos 2 θ ( sin 2 θ cos 2 θ ) cos 6 θ = 1 27 sin 6 θ 3 sin 2 θ cos 2 θ ( 1 3 ) cos 6 θ = 1 27 sin 6 θ cos 6 θ = 1 27 + sin 2 θ cos 2 θ = 1 27 + 1 4 sin 2 2 θ = 1 27 + 1 4 ( 1 cos 2 2 θ ) = 1 27 + 1 4 ( 1 1 9 ) = 7 27 \begin{aligned} \cos 2\theta & = - \frac 13 \\ \cos^2 \theta - \sin^2 \theta & = - \frac 13 \\ \sin^2 \theta - \cos^2 \theta & = \frac 13 \\ \left(\sin^2 \theta - \cos^2 \theta\right)^3 & = \left(\frac 13\right)^3 \\ \sin^6 \theta - 3\sin^4 \theta \cos^2 \theta + 3\sin^2 \theta \cos^4 \theta - \cos^6 \theta & = \frac 1{27} \\ \sin^6 \theta - 3\sin^2 \theta \cos^2 \theta (\sin^2 \theta - \cos^2 \theta) - \cos^6 \theta & = \frac 1{27} \\ \sin^6 \theta - 3\sin^2 \theta \cos^2 \theta \left(\frac 13\right) - \cos^6 \theta & = \frac 1{27} \\ \sin^6 \theta - \cos^6 \theta & = \frac 1{27} + \sin^2 \theta \cos^2 \theta \\ & = \frac 1{27} + \frac 14 \sin^2 2 \theta \\ & = \frac 1{27} + \frac 14 (1 - \cos^2 2 \theta) \\ & = \frac 1{27} + \frac 14 \left(1 - \frac 19 \right) \\ & = \boxed{\dfrac 7{27}} \end{aligned}

Philip Lee
Aug 14, 2017

Relevant wiki: Factorization of Polynomials

From the double angle identities and pythagorean identities , cos 2 θ = cos 2 θ sin 2 θ = 1 3 \cos2\theta=\cos^2\theta-\sin^2\theta=-\frac{1}{3} and sin 2 θ + cos 2 θ = 1 \sin^2\theta+\cos^2\theta=1 .

Hence, by reversing the perfect cube identity ,

sin 6 θ cos 6 θ = ( cos 6 θ sin 6 θ ) = [ ( cos 2 θ sin 2 θ ) 3 + 3 cos 4 θ sin 2 θ 3 cos 2 θ sin 4 θ ] = [ ( cos 2 θ sin 2 θ ) 3 + 3 cos 2 θ sin 2 θ ( cos 2 θ sin 2 θ ) ] = [ ( cos 2 θ sin 2 θ ) 3 + 3 4 ( 4 cos 2 θ sin 2 θ ) ( cos 2 θ sin 2 θ ) ] = { ( cos 2 θ sin 2 θ ) 3 + 3 4 [ ( cos 2 θ + sin 2 θ ) 2 ( cos 2 θ sin 2 θ ) 2 ] ( cos 2 θ sin 2 θ ) } = { ( 1 3 ) 3 + 3 4 [ ( 1 ) 2 ( 1 3 ) 2 ] ( 1 3 ) } = 7 27 \begin{aligned} \sin^6\theta-\cos^6\theta &= -\left(\cos^6\theta-\sin^6\theta\right) \\ &= -\left[\left(\cos^2\theta-\sin^2\theta\right)^3+3\cos^4\theta\sin^2\theta-3\cos^2\theta\sin^4\theta\right] \\ &= -\left[\left(\cos^2\theta-\sin^2\theta\right)^3+3\cos^2\theta\sin^2\theta\left(\cos^2\theta-\sin^2\theta\right)\right] \\ &= -\left[\left(\cos^2\theta-\sin^2\theta\right)^3+\frac{3}{4}\left(4\cos^2\theta\sin^2\theta\right)\left(\cos^2\theta-\sin^2\theta\right)\right] \\ &= -\left\{\left(\cos^2\theta-\sin^2\theta\right)^3+\frac{3}{4}\left[\left(\cos^2\theta+\sin^2\theta\right)^2-\left(\cos^2\theta-\sin^2\theta\right)^2\right]\left(\cos^2\theta-\sin^2\theta\right)\right\} \\ &= -\left\{\left(-\frac{1}{3}\right)^3+\frac{3}{4}\left[\left(1\right)^2-\left(-\frac{1}{3}\right)^2\right]\left(-\frac{1}{3}\right)\right\} \\ &= \frac{7}{27} \ _\square \end{aligned} or by factoring sin 6 θ cos 6 θ \sin^6\theta-\cos^6\theta directly,

sin 6 θ cos 6 θ = ( cos 2 θ sin 2 θ ) ( cos 4 θ + cos 2 θ sin 2 θ + sin 4 θ ) = ( cos 2 θ sin 2 θ ) [ ( cos 2 θ + sin 2 θ ) 2 cos 2 θ sin 2 θ ] = ( cos 2 θ sin 2 θ ) [ ( cos 2 θ + sin 2 θ ) 2 1 4 ( 4 cos 2 θ sin 2 θ ) ] = ( cos 2 θ sin 2 θ ) { ( cos 2 θ + sin 2 θ ) 2 1 4 [ ( cos 2 θ + sin 2 θ ) 2 ( cos 2 θ sin 2 θ ) 2 ] } = ( 1 3 ) { ( 1 ) 2 1 4 [ ( 1 ) 2 ( 1 3 ) 2 ] } = 7 27 \begin{aligned} \sin^6\theta-\cos^6\theta &= -\left(\cos^2\theta-\sin^2\theta\right)\left(\cos^4\theta+\cos^2\theta\sin^2\theta+\sin^4\theta\right) \\ &= -\left(\cos^2\theta-\sin^2\theta\right)\left[\left(\cos^2\theta+\sin^2\theta\right)^2-\cos^2\theta\sin^2\theta\right] \\ &= -\left(\cos^2\theta-\sin^2\theta\right)\left[\left(\cos^2\theta+\sin^2\theta\right)^2-\frac{1}{4}\left(4\cos^2\theta\sin^2\theta\right)\right] \\ &= -\left(\cos^2\theta-\sin^2\theta\right)\left\{\left(\cos^2\theta+\sin^2\theta\right)^2-\frac{1}{4}\left[\left(\cos^2\theta+\sin^2\theta\right)^2-\left(\cos^2\theta-\sin^2\theta\right)^2\right]\right\} \\ &= -\left(-\frac{1}{3}\right)\left\{\left(1\right)^2-\frac{1}{4}\left[\left(1\right)^2-\left(-\frac{1}{3}\right)^2\right]\right\} \\ &= \frac{7}{27} \ _\square \end{aligned}

Please post a solution if you have any easier ones :)

Philip Lee - 3 years, 10 months ago
Daniel Branscombe
Aug 16, 2017

using

S i n 2 ( θ ) = 1 C o s ( 2 θ ) 2 = 1 1 3 2 = 2 3 Sin^2(\theta)=\frac{1-Cos(2\theta)}{2}=\frac{1-\frac{-1}{3}}{2}=\frac{2}{3}

and

C o s 2 ( θ ) = 1 + C o s ( 2 θ ) 2 = 1 + 1 3 2 = 1 3 Cos^2(\theta)=\frac{1+Cos(2\theta)}{2}=\frac{1+\frac{-1}{3}}{2}=\frac{1}{3}

we get

S i n 6 ( θ ) = ( S i n 2 ( θ ) ) 3 = ( 2 3 ) 3 = 8 27 Sin^6(\theta)=(Sin^2(\theta))^3=(\frac{2}{3})^3=\frac{8}{27}

C o s 6 ( θ ) = ( C o s 2 ( θ ) ) 3 = ( 1 3 ) 3 = 1 27 Cos^6(\theta)=(Cos^2(\theta))^3=(\frac{1}{3})^3=\frac{1}{27}

Thus

S i n 6 ( θ ) C o s 6 ( θ ) = 8 27 1 27 = 1 27 Sin^6(\theta)-Cos^6(\theta)=\frac{8}{27}-\frac{1}{27}=\frac{1}{27}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...